Promoting lifelong learning: What marketers can learn from social capital theory - Mones, Reynaldo A. (Animo Repository, 2015)
Social Capital (SC) refers to the nature and extent of one’s participation in informal networks and formal civic organizations. It includes network access and forms of participation, namely: “bonding” and “bridging” social capital (Putnam, 2000). This research shares insights on how higher education institutions promote lifelong learning (LLL) through the SC theory. This study adapts Putnam’s definition of SC. The research proceeded by gathering demographics about students; measuring strength of bonding and bridging SC among post-baccalaureate students and teachers; and, correlating demographic data and SC strength in motivating students to complete the post-baccalaureate degree. We adapted the Social Capital Questionnaire of World Bank. We surveyed 151 respondents from De La Salle-College of Saint Benilde (DLS-CSB). Research findings are: rank and file and supervisory employees have higher motivation to pursue LLL than business owners and managers; cooperation among students increases the motivation of students to pursue LLL; and, there is a direct relationship between number of modules finished and motivation to pursue LLL. The implications are: using marketing campaigns related to work promotion targeted at rank and file employees stimulates enrollment and, activities that support interaction among students lead to completion of more courses, encouraging students to finish the entire diploma program.